Ethical and prophetic digital communication: Aḥsanu qaulān-based scaffolding service learning in SMEs empowerment - Rama Kertamukti; Nur Kareelawati Abd Karim; Rahmah Attaymini (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2026)
This study addresses the gap in digital communication education that often emphasizes technical skills while neglecting ethical formation and the growing importance of visual representation in digital environments. It examines how digital communication learning can be designed as an ethical and prophetic practice through a scaffolding-based service learning approach grounded in the principle of aḥsanu qaulān. Using a qualitative pedagogical case study, the research was conducted in an Anthropology and Brand Management course at UIN Sunan Kalijaga Yogyakarta, involving 140 students and 15 SMEs. Data were collected through observations, reflections, interviews, and digital artifacts. The findings show that staged scaffolding shifts students' understanding from technical production to context-sensitive, honest, and visually responsible communication. Students internalized aḥsanu qaulān in language, message claims, and visual representation. This study concludes that value-based scaffolding service learning effectively integrates ethical sensitivity, visual literacy, and professional competence in digital communication. The findings imply that digital communication courses should embed ethical checkpoints, staged feedback, and community-based digital projects into the curriculum, enabling students not only to produce persuasive digital content but also to practice accountable, culturally sensitive, and socially responsible communication for real community partners.